Obama's fractured legacy : the politics and policies of an embattled presidency - Vergniolle de Chantal, François (New perspectives on the American presidency., 2020)
Featuring a range of experts on the American presidency, this book offers both European and American perspectives on both the successes and failures of President Obama's tenure in the White House. Focusing primarily on domestic policy, these essays explain why Obama's widely anticipated moment of change did not fully materialise.